Circadian clock gene CRY2 degradation is involved in chemoresistance of colorectal cancer - Fang, Lekun (Mol Cancer Ther, 2015)
Biomarkers for predicting chemotherapy response are important to treatment of colorectal cancer (CRC) patients. Cryptochrome 2 (CRY2) is a circadian clock protein involved in cell cycle, but the biological consequences of this activity in cancer are poorly understood. We set up biochemical and cell biology analyses to analyze CRY2 expression and chemoresistance. Here we report that CRY2 is overexpressed in chemoresistant CRC samples, and CRY2 overexpression is correlated with poor patient survival. Knockdown CRY2 increased colorectal cancer sensitivity to oxaliplatin in colorectal cancer cell. We also identify FBXW7 as a novel E3 ubiquitin ligase for targeting CRY2 through proteasomal degradation. Mechanistic studies show that CRY2 is regulated by FBXW7, in which FBXW7 binds directly to phosphorylated Thr300 of CRY2. Furthermore, FBXW7 expression leads to degradation of CRY2 through enhancing CRY2 ubiquitination and accelerating CRY2’s turnover rate. High expressed FBXW7 downregulates CRY2 and increases colorectal cancer cells sensitivity to chemotherapy. Low FBXW7 expression is correlated with high CRY2 expression in CRC patient samples. Also, low FBXW7 expression is correlated with poor patient survival. Taken together, our findings indicate that the upregulation of CRY2 caused by downregulation of FBXW7 may be a novel prognostic biomarker and may represent a new therapeutic target in colorectal cancer.